2002
DOI: 10.1001/archneur.59.10.1572
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Brain Volume Measurement in Multiple Sclerosis

Abstract: The rate of development of brain atrophy is largely independent of the course of the disease and other clinical characteristics. The relentless loss of tissue occurring in MS is not restricted to later (progressive) phases of the disease, thereby stressing the need for early neuroprotective treatment in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
33
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(42 citation statements)
references
References 26 publications
8
33
0
1
Order By: Relevance
“…Our findings of faster whole brain atrophy in SPMS, PPMS, and RRMS than CIS, who, in turn, showed higher cortical atrophy than HCs, are similar to previous studies on longitudinal whole brain atrophy,5, 53, 54 regional atrophy,17, 55, 56, 57 and pathology of MS phenotypes,2, 47 Our study confirms our previous findings that relationships between whole brain atrophy and clinical changes are weak or absent5 and shows DGM atrophy as a stronger marker of clinical disability. Although the GM volumes of cortical lobes could not predict future EDSS progression, the more detailed post‐hoc analyses showed that regional volumes, such those of the hippocampus and the angular gyrus, were associated with future EDSS progression.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings of faster whole brain atrophy in SPMS, PPMS, and RRMS than CIS, who, in turn, showed higher cortical atrophy than HCs, are similar to previous studies on longitudinal whole brain atrophy,5, 53, 54 regional atrophy,17, 55, 56, 57 and pathology of MS phenotypes,2, 47 Our study confirms our previous findings that relationships between whole brain atrophy and clinical changes are weak or absent5 and shows DGM atrophy as a stronger marker of clinical disability. Although the GM volumes of cortical lobes could not predict future EDSS progression, the more detailed post‐hoc analyses showed that regional volumes, such those of the hippocampus and the angular gyrus, were associated with future EDSS progression.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, they found no correlation between the baseline EDSS or the annualised DEDSS score and annualised markers of brain atrophy. 13 Similarly, we did not find any significant differences between the three MS courses and atrophy rate in our study. In a recent longitudinal study, Pagani et al 38 showed that brain atrophy develops involving different structures in different MS courses, corpus callosum atrophy being typical for RRMS.…”
Section: Discussionsupporting
confidence: 44%
“…7 In contrast with focal MS lesions, atrophy measures of the brain or spinal cord have been regarded as a better predictor of the disability progression in MS. 2 5 8-10 However, some reports also show non-significant correlation between disability and atrophy. [11][12][13][14][15][16] Focal MS lesions visualised on MRI have a characteristic pattern of oval-shaped, typically periventricular white matter changes, often located in the corpus callosum. Atrophy of the corpus callosum is common in MS.…”
mentioning
confidence: 99%
“…Although being male has been proposed as a risk factor for cognitive impairment in MS patients [5], the results on brain neuropathological MS indices are conflicting, some studies have suggested a higher degree of brain damage in males [6][7][8], while others have failed to replicate these findings [9,10]. As these conflicting results might derive from gender interacting with other relevant demographic and clinical variables, we explored whether female and male MS patients, carefully matched for age, years of disease, level of education, intelligence quotient (IQ), neuropsychological performance and physical disability, differed in two indices of MS progression: gray matter (GM) atrophy and resting state functional connectivity (FC) changes.…”
Section: Introductionmentioning
confidence: 99%